KARAKTERISTIK BUBUR PEDAS DALAM KEMASAN KALENG [The Characteristics of Spicy Porridges In the Can Packaging] - Iwan Rusiardy; Sedarnawati Yasni; Elvira Syamsir (Jurnal Teknologi dan Industri Pangan, 2014)
Spicy porridge is a traditional food from West Kalimantan that has unique flavor and aroma from the various spices and vegetables. Distinctive aroma comes from the kesum leaves (Polygonum minus huds) and spices which is used as a mixture of cuisines and have bioactive activity. The objective of this study was to obtain scientific evidence regarding the formulation and nutritional value of canned spicy porridge without vegetables for humans based on emergencies food with flavor and taste appropriate with the Indonesian people. The study was conducted in three phases namely the spice formulation, kesum leaves formulation and condition of spicy porridge that would canned formulation. The results show that the most preferred product with the composition 66.9% toasted rice, 22.4% peanuts, 10.7% palm oil and 43.5% mixture spices accompanied by the addition of the 2.5% kesum leaves. The most preferred spicy porridge in the can packaging from the half cooked rice with the Fo value are 9.141 minutes and sterillized for 60 minutes on 121°C. The energy distribution of calories 50.07 ± 3.54% from carbohydrates, 36.53 ± 3.04% from fat and 13.40 ± 0.69 % from protein. Based on calory distribution and prefer level test, spicy porridge in can packaging is compliant and can be used as emergency food alternative in Indonesia.